To solve the equation in your steps:
Step 1: \(-3x - 5 = 13\)
In Step 2, you isolate the term involving \(x\) by adding \(5\) to both sides, which is the addition property of equality:
\[ -3x - 5 + 5 = 13 + 5 \] This simplifies to: \[ -3x = 18 \]
In Step 3, you solve for \(x\) by dividing both sides by \(-3\), which is the division property of equality:
\[ x = \frac{18}{-3} \] This simplifies to: \[ x = -6 \]
Thus, the sequence of inverse operations used for steps 2 and 3 is:
the addition property of equality and then the division property of equality.